ANALISIS LITERATUR : MEDIA PERMAINAN EDUKATIF INTERAKTIF DALAM MENINGKATKAN MOTIVASI BELAJAR PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Amalya Cantika; Endang M Kurnianti; Susi Winarni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the role of interactive educational game media in increasing students' learning motivation in Social Sciences (IPS) subjects in elementary schools through a literary study approach. The background of the study is based on the low interest of students in learning IPS which still uses many conventional methods such as lectures. In facing these challenges, interactive learning media, especially educational games, are considered capable of creating a more enjoyable, meaningful, and contextual learning atmosphere. This study was conducted by reviewing various sources of literature from journals and relevant research reports in the last 5-10 years. The results of the analysis show that the use of interactive educational game media has a positive and significant effect on increasing students' learning motivation, both through increasing active involvement, learning interest, and learning outcomes. Thus, the application of interactive educational game media is an effective learning strategy to increase learning motivation in IPS learning at the elementary school level, and can be an innovative solution in creating a more lively and relevant learning experience for students.